Expression of the cloned uvrB gene of Escherichia coli: dependency on nonsense suppressors. - Pannekoek, H (1979)
Recombinant plasmid pNP5, consisting of plasmid pMB9 on which the uvrB gene is cloned, fully complements for the defects due to chromosomal uvrB mutations in the presence of the amber suppressor sup-6 or supF. Correndonuclease II activity was also completely restored in in UvrB strains containing both plasmid pNP5 and amber suppressor sup-6, as compared with the parental UvrB+ strain. It is shown that the amber mutation which interferes with the expression of the cloned uvrB gene is located outside this gene. Apparently, the amber mutation exerts a polar effect on uvrB expression that is relieved by sup-6 or supF. Introduction of a rho mutation into suppressor-free UvrB strains, harboring pNP5, did not relieve the polarity caused by the amber mutation.